Antioxidant Activity and Sensory Profile Characterization of Herbal Tea Made of Melinjo (Gnetum gnemon L.) Peels and White Turmeric (Curcuma zedoaria) - Alifah Lailatul Rahmah; Dase Hunaefi; Nancy Dewi Yuliana (The University of Lampung, 2026)
Melinjo peel, a by-product of melinjo cracker production, has the potential to become waste if not utilized optimally. Howeever, it contains bioactive compounds that can be processed into herbal tea bags with health benefits. Melinjo peel has relatively low antioxidant activity; therefore, the addition of other ingredients, such as white turmeric is necessary to enhance the functional value of the herbal tea. Herbal tea bags generally have a slightly bitter and astringent taste; thus, stevia leaves were added as a natural sweetener. Formula optimization of the herbal tea was carried out using response surface methodology (RSM), with total flavonoid content and antioxidant activity as the measured responses. The optimal formula was further subjected to sensory profile characterization (RATA method and hedonic rating) to determine the selected formulation. The selected herbal tea formula consisted of 50% melinjo peel, 40% white turmeric, and 10% stevia leaves. Based on the RATA test, the herbal tea was characterized by attributes of licorice, sweet, floral, bitter aftertaste, astringency, and metallic aftertaste, with an average liking score of 3.51 (liked).